Studi Kelayakan Penggunaan Cangkang Kemiri Sebagai Pengganti Sebagian Agregat Kasar Terhadap Mutu Beton - Haris, H. (Civil Engineering Department, Tadulako University, 2020)
In the current era of globalization, the development of concrete in the construction sector is very rapid, be it housing, offices, bridges, roads, dams, ports, and others. That is inseparable from the use of concrete as a part of building construction. The use of coarse aggregate for concrete mixes, namely natural stone, is a non-renewable natural resource. Therefore an alternative is needed as a substitute. One of the natural resources that can be renewed is hazelnut skin. Candlenut is a traditional plant that has various benefits, one of which is a candlenut shell. In this study, the materials used for standard concrete mixtures consist of water, cement, fine aggregate, and coarse aggregate. The water used for mixing the concrete is taken from the PDAM channel. The results showed that the effect of candlenut shells used as a substitute for some coarse aggregate decreased compressive strength results from the results of standard concrete compressive strength. The results obtained by the value of standard concrete compressive strength at 28 days of concrete were 27.19Mpa for concrete using Candlenut shells of 20% produce a compressive strength value of 17.33 Mpa at 28 days of concrete. 35% produce a concrete compressive strength value of 16.04 Mpa, while 50% produce a concrete compressive strength value of 15.17 Mpa. Thus the research shows that more and more candlenut shells are being used as a substitute for coarse aggregate in the concrete mixture.